2014
DOI: 10.1590/1982-0216201417612
|View full text |Cite
|
Sign up to set email alerts
|

Comparação das formas de aplicação papel e caneta e eletrônica do índice de estresse parental versão reduzida (PSI-SF)

Abstract: 16 (2): [413][414][415][416][417][418][419][420][421] aids and auditory rehabilitation. Pediatric hearing healthcare programs have emphasized the importance of a family centered approach, since family's participation on the early diagnosis and intervention brings better results to children 1 .In general, after a child is diagnosed with hearing impairment, the family goes through a difficult period, having to deal with strong feelings of inadequacy, anger, guilt, vulnerability and confusion 2 . Besides, the nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
(12 reference statements)
1
2
0
Order By: Relevance
“…Regarding the first implementation of the PSI-SF, the experimental group was observed to have lower scores than the control group; however, these differences were not significant ( Figure 1). The scores of this study were similar to those found when the PSI-SF was applied to Brazilian parents of children with typical development and no hearing complaints (10) . Initially, the mean stress levels of participants were expected to be higher.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Regarding the first implementation of the PSI-SF, the experimental group was observed to have lower scores than the control group; however, these differences were not significant ( Figure 1). The scores of this study were similar to those found when the PSI-SF was applied to Brazilian parents of children with typical development and no hearing complaints (10) . Initially, the mean stress levels of participants were expected to be higher.…”
Section: Discussionsupporting
confidence: 82%
“…The permission from the copyright holders of PSI-SF was obtained to perform adaptations of some expressions to Brazilian Portuguese. An initial study (10) showed that the PSI-SF could be applied electronically.…”
Section: Resultsmentioning
confidence: 99%
“…The present study utilized the European–Portuguese version of the PSI available from the publisher. As was done previously, some expressions were culturally adapted for use with our Brazilian Portuguese sample (Aiello et al, 2014). Cronbach's α value for the Total Stress score was 0.89.…”
Section: Methodsmentioning
confidence: 99%